Self-Efficacy of EFL Pre-Service Teachers in China: A Mixed Methods Approach - Cui, Han; Chen, Xin; Li, Shujun; Liu, Honggang (Social Education Research, 2025)
Language teacher self-efficacy has been widely researched in the past decades. However, less attention has been paid to the pre-service teachers’ self-efficacy during their teaching practicum. In order to fill this gap, the current research used a mixed-methods approach to investigate self-efficacy of english as a foreign language (EFL) preservice teachers in China and explored the contributing factors to their self-efficacy. Specifically, the EFL Pre-service Teacher Self-Efficacy Scale was distributed to a sample of 59 student teachers. Two participants from the survey sample participated in semi-structured interviews. The results indicated that self-efficacy in EFL pre-service teachers was high, and no significant differences in self-efficacy were observed across different grades. The contributing factors to EFL pre-service teachers’ self-efficacy were diverse, including introspection and emotional transfer, internship experience and teaching practice, feedback and encouragement, observing the success of others, success stories and overcoming challenges, emotional and physical states, and professional knowledge and skills. According to the results, some implications for improving the self-efficacy of EFL pre-service teachers were provided.